Apocrine Carcinoma Developing in a Naevus Sebaceous of Scalp - Paudel, Upama; Jha, A; Pokhrel, DB; Gurung, D; Parajuli, S; Pant, A (Kathmandu University Medical Journal, 2013)
Apocrine skin carcinoma is an aggressive cutaneous tumour. We report a case of apocrine carcinoma developing in a naevus sebaceous of scalp in a 45 years old male. Malignant transformation of Naevus sebaceous is a rare complication usually found in elderly patients. Most of these tumours are basal cell carcinoma or squamous cell carcinoma. Only few cases of apocrine carcinoma on naevus sebaceous have been previously reported. This report highlights the potential of naevus sebaceous for malignant transformation. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 103-105 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7356